PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO, RETURN ON EQUITY, NET PROFIT MARGIN DAN EARNING PER SHARE TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2015) - Aini Umi Kholifah, 13.05.52.0123; Wahyudi, Djoko (Students Journal of Accounting and Banking, 2017)
This study aims to analyze the Influence of Current Ratio, Debt To Equity Ratio, Return On Equity, Net Profit Margin, and Earning Per Share Against Stock Price studies at manufacturing companies listed on the Indonesia Stock Exchange Year 2013-2015.Â The sample in this research is 252, sample selection is done by purposive sampling method. Data were analyzed by using skewness-kurtosis normality test, classic assumption test, coefficient determination test, F test and hypothesis test.Â The result of analysis shows that the variable of current ratio have positive significant effect to stock price, debt to equity ratio have positive significant effect to stock price, return on equity variable have positive effect to stock price, net profit margin variable has negative effect to stock price and earnings per variable Share positively affects the share price at the Manufacturing Company listed on the Indonesia Stock Exchange.Keywords: Current Ratio, Debt To Equity Ratio, Return On Equity, Net Profit Margin and Earning Per Share Against Stock Price